Sifat Dielektrik Campuran Gas CO2 Dengan Nitrogen (N2) Dibawah Terpaan Medan Tinggi DC Polaritas Positif - Michael Anderson; Fri Murdiya (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Sulfur hexafluoride gas (SF6) is widely used in the power electrical system such as circuit breaker, gas insulated switchgear (GIS) and gas insulated line (GIL). However, this gas has negative impacts such as global warming, so we need to find other gases as alternative gas for example is carbon dioxide (CO2) and nitrogen (N2) that it is more friendly environmental materials. This research discusses about dielectric characteristics of mixture of carbon dioxide gas (CO2) and nitrogen (N2) gas under pressure high voltage in positive polarity. This experiment aims to estimate the breakdown voltage in mixture of carbon dioxide gas (CO2) and Nitrogen (N2). This experiment was carried out by using sphere electrodes and needle-rod electrodes. The result is indicated that the breakdown voltage in gas with sphere electrodes is greater than with needle-rod electrodes and then space electrodes are proportional to breakdown voltage in gas insulation.Keywords : electrodes, mixture gas insulation, breakdown voltage, positive polarity